الكرة الطائرة - تباني، علي (University of M'sila Mohamed Boudiaf, 2023)
الملخص : بالعربية : لقد اعتمد مقياس الكرة الطائرة كأحد المقاييس الهامة المرتبطة ارتباطاً كبيراً وواضحاً بتخصص الموارد البشرية و تسيير المنشآت الرياضية لطلبة الادارة وتسيير رياضي وبالتحديد كمقياس للسداسي الرابع من السنة الثانية ليسانس لطلبة التخصص المذكور، والذي يتضمن خمسة محاور، الأول تاريخ وفلسفة النشاط ومميزات وطبيعة اللعبة، والثاني تناولنا فيه المهارات الأساسية في الكرة الطائرة تأديتها والأخطاء الشائعة في حين المحور الثالث تطرقنا فيه إلى أشكال التحضير وتعليم المهارات الأساسية في الكرة الطائرة الإعداد والسحق، أماالمحور الرابع أوردنا فيه طرق تعلم المهارات الأساسية وعوائقها، المحور الخامس جاء فيه الاعداد النفسي في الكرة الطائرة، خطط اللعب في الكرة الطائرة، الانتقاء في الكرة الطائرة، وكذلك التخطيط والبرمجة واخيرا تقييم وتقويم الصفات البدنية أهداف المقياس: وتتضح أهداف هذا المقياس بشكل جلي عند الخوض في تفاصيل محاوره التي تعنى بكل الجوانب العلمية والمعرفية والمهارية والتدريبية والنفسية المرتبطة بالكرة الطائرةوتتضح اهداف المقياس من خلال ما يلي: الهدف العام: أن يطلع الطالب على تاريخ وأهم النظريات والمحطات المختلفة على طبيعة الكرة الطائرة ووظائف أعضاء الجسم وان يتوصل في نهاية دراسته للمقياس (السنة الثانية الكرةالطائرة) على فهم المعارف النظرية والمهارات الاساسية من تمرير واعداد وسحق وصد وكيفية تطبيقها فيالأعمال التطبيقية أثناء التدرب أو أثناء تعليمها للطلبة. الأهداف الخاصة: - معرفة القواعد الأساسية النظرية والتطبيقية المرتبطة بالكرة الطائرة. - أن يعرف المهارات الأساسية في اللعبة وكيفية أدائها وتعليمها للطلبة. - أن يميز بين مختلف المهارات وكيفية تعليمها بمراحلها على أسس علمية صحيحة Searchlight in English The volleyball scale has been adopted as one of the important scalesthat are closely and clearlylinked to the specialization of humanresources and sports facilities management for students of management and sports management, specifically as a scale for the fourthsemester of the second year of the bachelor'sdegree for students of the aforementionedspecialization, whichincludes five axes. The first is the history and philosophy of the activity and the features and nature of the game. The second is the basic skills in volleyball, their performance and commonmistakes. The third axis is the forms of preparation and teaching basic skills in volleyball, preparation and crushing. The fourth axis is the methods of learning basic skills and their obstacles. The fifth axis includespsychologicalpreparation in volleyball, game plans in volleyball, selection in volleyball, as well as planning and programming, and finallyevaluation and assessment of physicalqualities. Objectives of the scale: The objectives of thisscalebecomeclearwhendelvinginto the details of its axes, which deal with all the scientific, cognitive, skill, training and psychological aspects related to volleyball. The objectives of the scalebecomeclearthrough the following: General objective: The studentshouldbeinformed about the history and most important theories and different stations on the nature of volleyball and the functions of the body'sorgans and reachAt the end of hisstudy of the course (second year volleyball) to understand the theoreticalknowledge and basic skills of passing, preparing, crushing and blocking and how to applythem in practicalworkduring training or whileteachingthem to students. Specificobjectives: - Knowing the basic theoretical and practicalrulesrelated to volleyball. - Knowing the basic skills in the game and how to perform and teachthem to students. - Distinguishingbetween the differentskills and how to teachthem in their stages on correct scientificfoundations
Keywords: الكرة الطائرة; المهارات الاساسية في الكرة الطائرة; 3الاستعداد التمرير الاعداد السحق الصد